Pengaruh Pembelajaran Berbasis Masalah dan Media Pembelajaran Berbasis Online Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Pemasaran Online Kelas XI di SMK Negeri 2 TONDANO - Natalia S. N Larumpa; Consuslasia Korompis; Sem Dehop (Jurusan Pendidikan Ekonomi Fakultas Ekonomi dan Bisnis UNIMA, 2020)
This study aims to determine the effect of problem-based learning and online-based learning media on student learning outcomes in online marketing subjects in class XI at SMK Negeri 2 TONDANO. The research method used in this research is the experimental method. Based on the research it is known that student learning outcomes using the Problem Based Learning Model in class XI Marketing 1 SMK N 2 Tondano have increased. There are differences in student results through test results using Problem Based Learning Model (Problem Based Learning). So there is an increase in student learning outcomes by using the Problem Based Learning Model (Problem Based Learning). Based on the research, it is known that student learning outcomes using online-based learning media in class X1 marketing at SMk N 2 Tondano have increased after the application of the use of online-based learning media. There are differences in student results through test results using online-based learning media. So there is an increase in student learning outcomes using online-based learning media